Investigator‐initiated clinical study of a functional peptide, SR‐0379, for limb ulcers of patients with Werner syndrome as a pilot study. Issue 11 (20th November 2019) - Nakagami, Hironori; Sugimoto, Ken; Ishikawa, Takahiro; Koshizaka, Masaya; Fujimoto, Taku; Kiyohara, Eiji; Hayashi, Misa; Nakagawa, Yukinobu; Ando, Hiroshi; Terabe, Yuta; Takami, Yoichi; Yamamoto, Koichi; et al.
Abstract : Aim: An investigator‐initiated clinical study was carried out to evaluate the therapeutic potency of SR‐0379 for the treatment of leg ulcers in patients with Werner syndrome. Methods: A multicenter, open‐label study was carried out from September 2017 to February 2018. The inclusion criteria for leg ulcers were: (i) leg ulcers in patients with Werner syndrome, diabetes or critical limb ischemia/venous stasis; and (ii) a wound size of >1 cm and <6 cm in diameter. Four individuals with Werner syndrome and diabetic ulcers, respectively, were enrolled. SR‐0379 (0.1%) was sprayed on skin ulcers once per day for 4 weeks. Efficacy was evaluated by determining the rate of wound size reduction as a primary end‐point at 4 weeks after the first treatment compared with the pretreatment wound size. As secondary end‐points, the DESIGN‐R score index, the 50% wound size reduction ratio, time to wound closure and quantification of wound bacteria were also evaluated. The safety of SR‐0379 was evaluated during the study period. Results: The reduction rate of ulcer size treated with 0.1% SR‐0379 was 22.90% (mean) in the Werner syndrome ulcers group ( n = 4) and 35.70% (mean) in the diabetic ulcers group ( n = 4), respectively. The DESIGN‐R score decreased by 4.0 points in the Werner syndrome ulcers group and 4.3 points in the diabetic ulcers group. Two mild adverse events were reported in two patients, and causal relationships were denied in any events. Conclusion: Treatment with SR‐0379 was safe, well‐tolerated, and effective for leg ulcers of both Werner syndrome and diabetes patients. Geriatr Gerontol Int 2019; 19: 1118–1123 .